Mulheres Letradas e Missionárias da Luz: formação da Professora nas Escolas Normais do Ceará - 1930 a 1960 - Araújo, Fátima Maria Leitão (2006)
The present research aims at studying teaching staff formation proposals for Teachers’ Training Rural Schools in Ceará from 1930 to 1960. Our purpose is to observe the discrepancies between government discourse and oficial documents and the everyday teacher-classroom practice. The research has helped us to evaluate teacher formation proposals at Rural Schools belonging to the social political context of post 1930 (President Vargas Era), and understand the role of the project in defining the ideal teacher profile for the rural area. To achieve these goals we have analyzed the ideas, experiences, practices, representations and the place reserved for rural area teachers at he beginning of the 20th century. We based our research on oral and written speeches, reports, public and private files and official documents among others. For us, the individual oral speeches were one of the most important sources for the research carried out since one of our concerns was to (re)construct the history from the point of view of teachers at the time period analyzed. Among the people who had an important part in the Teachers Training Rural Schools program we highlight the role played by women teachers, educators and missionaries who had the hard task of enlightening the country areas by means of primary education.